Properties of graphene composite fiber seamless knitted fabric and its application in boxing training - Liu, Tianyue (Frontiers in Materials, 2023)
In boxing, the wrong training methods can easily cause physical injury, so many sports protective clothing will use new materials to reduce the impact of boxing training. The aim of this paper is to design a boxing suit based on graphene composite fiber seamless knitted fabric, so as to reduce the injury of boxers during training. In this paper, the head yarn, inner yarn and knitting structure of graphene composite fiber seamless knitted fabrics are discussed, and nine kinds of fabrics are determined by orthogonal matrix method; then, a comprehensive evaluation of the wear resistance of fabrics was proposed based on sequence entropy weight technology, and the ideal solution similarity (TOPSIS) method was used to calculate the wear resistance; finally, this paper designed the boxing protective suit according to the best combination of performance. The experimental results in this paper showed that the veil of sample No. 7 is 70D/48F graphene nylon, the inner yarn is 30D graphene spandex/70D graphene nylon covered yarn, and the fabric with the knitted structure of 1 + 3 false rib has the best comprehensive performance and the highest relative proximity, reaching 0.862. The actual wearing test proves that the comfort of anti-impact boxing suit is slightly better than that of ordinary boxing suit. The clothing designed in this paper has good anti-impact effect. Therefore, on the whole, the boxing suit with graphene composite fiber seamless knitted fabric has good protective effect and can be used for boxing training.